The Social Consequences of Legal Principles: Investigating the Origins of Squatting in Sri Lanka’s Land Settlement Schemes - Paranage, Kavindra (European Scientific Journal, ESJ, 2017)
This research tries to understand the reasons for the continuing presence of squatters in Sri Lanka’s state-sponsored land settlement schemes. A preliminary review of the literature pertaining to this area suggests that the legal and regulatory framework in these settlements may be the cause that trigger the necessary social preconditions required for squatter settlements to come into existence. In trying to test this hypothesis found in the literature, the present paper undertakes a qualitative historical analysis into a sample village where squatter settlements are most profoundly observed. Data is collected from three main sources: interviews conducted with key informants in the sample village, focus group discussions conducted with a mixed group of stakeholders as identified through key informants and, an exhaustive analysis of legal documents concerning land ownership and distribution as well as population-related statistics, land utilization patterns and village infrastructure. The analysis of the data proves the hypothesis as accurate by revealing that the central reason for the existence of squatters in the sample village is the legal restriction pertaining to minimum subdivisions by virtue of the Land Development Ordinance (1935) among other statutory provisions. This restriction prohibits owners from apportioning title to their land; they may only transfer title subject to the condition that such a transfer will not divide or otherwise fraction the property. Such restrictions serve to create a ‘social space’ where a number of second and third generation settlers are effectively left without a lawful claim to land, with encroaching on their siblings’ property or government property becoming the only available recourse.